PREDIKSI HARGA SAHAM MENGGUNAKAN GEOMETRIC BROWNIAN MOTION - Yeti Rosita (PRISMAKOM, 2021)
The rapid development of the economy, financial technology and the internet in recent years, resulted in more and more people starting to invest into the stock market. The problem is, changes in stock prices are often unexpected. Therefore, it requires accurate prediction of stock price changes in order to reduce investment risk and effectively increase investment returns. Forecasting stock prices can provide great benefits for the economic sector because the ability to predict future stock prices can help related parties prepare for expected conditions. One method that can be used to predict changes in stock price is the Geometric Brownian Motion method. Based on the results of calculations and tests using MAPE it can be concluded that changes in stock prices can be predicted using Geometric Brownian Motion.